A Green Synthesis of Polylimonene Using Maghnite-H+, an Exchanged Montmorillonite Clay, as Eco-Catalyst - Hodhaifa Derdar; Mohammed Belbachir; Amine Harrane (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
A new green polymerization technique to synthesis polylimonene (PLM) is carried out in this work. This technique consists of using Maghnite-H+ as eco-catalyst to replace Friedel-Crafts catalysts which are toxics. Maghnite-H+ is a montmorillonite silicate sheet clay which is prepared through a simple exchange process. Polymerization experiments are performed in bulk and in solution using CH2Cl2 as solvent. Effect of reaction time, temperature and amount of catalyst is studied, in order to find the optimal reaction conditions. The polymerization in solution leads to the best yield (48.5%) at -5°C for a reaction time of 6 h but the bulk polymerization, that is performed at 25°C, remains preferred even if the yield is lower (40.3%) in order to respect the principles of a green chemistry which recommend syntheses under mild conditions, without solvents and at room temperature. The structure of the obtained polymer (PLM) is confirmed by FT-IR and Nuclear Magnetic Resonance of proton (1H-NMR). The glass transition temperature (Tg) of the polylimonene is defined using Differential Scanning Calorimetry (DSC) and is between 113°C and 116°C. The molecular weight of the obtained polymer is determined by Gel Permeation Chromatography (GPC) analysis and is about 1360 g/mol. Copyright © 2019 BCREC Group. All rights reserved